1997
DOI: 10.1105/tpc.9.4.583
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose control of phytochrome A signaling in Arabidopsis.

Abstract: The expression of the Arabidopsis plastocyanin (PC) gene is developmentally controlled and regulated by light. During seedling development, PC gene expression is transiently induced, and this induction can be repressed by sucrose. In transgenic seedlings carrying a PC promoter-luciferase fusion gene, the luciferase-induced in vivo luminescence was similarly repressed by sucrose. From a mutagenized population of such transgenic seedlings, we selected for mutant seedlings that displayed a high luminescence leve1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(56 citation statements)
references
References 46 publications
2
54
0
Order By: Relevance
“…The latter include screens based on transgenic lines containing fusions of sugar-responsive promoters to reporter genes or selection markers. For instance, sucrose uncoupled mutants contain a luciferase reporter gene driven by the plastocyanin promoter (Dijkwel et al 1997); the impaired sucrose induction (isi) mutants contain the ApL3 promoter fused to a negative selection marker, the bacterial cytochrome P 450 gene (Rook et al 2001); the reduced sucrose response (rsr) mutants contain the potato patatin promoter combined with the b-glucoronidase gene (Martin et al 1997). These distinct approaches based on the effects of high sugar media on seedling development or on changes in the activity/expression of sugar-responsive genes, yielded overlapping mutants.…”
Section: Screens Based On Sugar-induced Arrest Of Early Developmentmentioning
confidence: 99%
“…The latter include screens based on transgenic lines containing fusions of sugar-responsive promoters to reporter genes or selection markers. For instance, sucrose uncoupled mutants contain a luciferase reporter gene driven by the plastocyanin promoter (Dijkwel et al 1997); the impaired sucrose induction (isi) mutants contain the ApL3 promoter fused to a negative selection marker, the bacterial cytochrome P 450 gene (Rook et al 2001); the reduced sucrose response (rsr) mutants contain the potato patatin promoter combined with the b-glucoronidase gene (Martin et al 1997). These distinct approaches based on the effects of high sugar media on seedling development or on changes in the activity/expression of sugar-responsive genes, yielded overlapping mutants.…”
Section: Screens Based On Sugar-induced Arrest Of Early Developmentmentioning
confidence: 99%
“…A number of growth and developmental processes have been found to depend on sucrose signaling (Dijkwel et al 1997;Chiou and Bush 1998;Roldan et al 1999). In wheat and other cool temperate grasses, conditions that favor sucrose accumulation such as low temperatures or illumination of detached leaves lead to the induction of fructan synthesis (Pontis 1989;Wagner et al 1986;Müller et al 2000;Nagaraj et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the PHYA is tissue-specific expressed in KFJT-1. Previous study on Arabidopsis suggested that sucrose could depress expression of PHYA (Dijkwel et al, 1997). Thus, we conferred that the down-regulated PHYA in young stem in KFJT-1 was due to high content of sucrose which mutual adjusted by the gene 3.2.1.26 and 2.4.1.13.…”
Section: Tissue-specific Gene Expression In the Development Of The Sementioning
confidence: 85%